Effect of Different Postharvest Treatments on Prolonging Shelf life of Citrus reticulata Blanco - Joshi, Pabitra; Ojha, Bishnu Raj; Kafle, Arun (Nepalese Horticulture, 2020)
This study was conducted during January to April 2018 to evaluate the effect of different postharvest treatments on maintaining quality and shelf life of mandarin. Laboratory experiment was conducted under Complete Randomized Design (CRD) with four replications and seven treatments (T1 = Control i.e. dipped in distilled water, T2 = Cinnamon oil @ 2%, T3 = Eucalyptus oil @2%, T4 = Calcium chloride @1%, T5 = Bavistin @0.1%, T6 = Paraffin Wax @10%, T7 = Paraffin Wax @ 10% + Bavistin @0.1%). Data were recorded in every 2 days interval and the final data was taken in 13 days interval because of the limited destructive sample. Postharvest treatment with wax @10% in combination with Bavistin @0.1% had minimum physiological loss in weight (6.61%) and maximum juice recovery percentage (43.72%) which was statistically at par with wax (10%), Bavistin (0.1%), Cinnamon oil (2%), Eucalyptus oil (2%) and Calcium chloride (1%) treated fruits. Also at the end of storage period the highest Total soluble solute(TSS) content (15.45°Brix) was recorded in Calcium chloride (1%) treated fruits which were statistically at par with control, Eucalyptus oil (2%), Bavistin (0.1%) treated fruits. The pH was found non-significant throughout the storage period whereas postharvest life was found the maximum (73 Days) in fruits treated with wax (10%) in combination with Bavistin (0.1%) while it was only 46 days in control.